1995
DOI: 10.1159/000133917
|View full text |Cite
|
Sign up to set email alerts
|

Physical mapping of 3 candidate tumor suppressor genes relative to Beckwith-Wiedemann syndrome associated chromosomal breakpoints at 11p15.3

Abstract: A physical map encompassing the 3 Mb region containing the breakpoints of two Beckwith-Wiedemann Syndrome patients at chromosome band 11p15.3 is presented. The candidate tumor suppressor genes WEE1 ST5, and rhombotin, are positioned on this map relative to these Beckwith-Wiedemann syndrome translocation and inversion breakpoints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Current maps in the databases are still controversial on the order of 11p15.3 genes. The mapping data presented here settles the debate whether LMO1 is more centromeric compared to WEE1 as proposed by Redeker et al (1995), or more telomeric as proposed by Higgins et al (1994) and confirmed by our results.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Current maps in the databases are still controversial on the order of 11p15.3 genes. The mapping data presented here settles the debate whether LMO1 is more centromeric compared to WEE1 as proposed by Redeker et al (1995), or more telomeric as proposed by Higgins et al (1994) and confirmed by our results.…”
Section: Resultssupporting
confidence: 89%
“…It probably functions as a transcriptional regulator because of its conserved cysteine-rich region homologous to the LIM domains (Boehm et al, 1990). Although all three genes are involved in important cellular functions and are located in the BWSCR3, none of the genes was directly implicated in BWS (Redeker et al, 1995). Furthermore, 11p allelotyping in different lung cancer cell lines revealed frequent allele loss in the discussed 11p15.3 region, with exception of the ST5 gene (Bepler and Koehler, 1995), supporting the location of a potential tumor suppressor region in 11p15.3.…”
Section: Copyright © 2001 S Karger Ag Baselmentioning
confidence: 90%
See 1 more Smart Citation
“…The CTR9 gene has been localized to chromosome 11p15 (Figure 3d). The 11p15.3 locus contains chromosomal aberrations associated with the pathogenesis of different tumor types including lung cancer and leukemia (Redeker et al, 1995). Interestingly, the Ctr9 gene locus is found to be deleted in pancreatic cancer (Bashyam et al, 2005) (Table 3).…”
Section: Leo1: Interacts With B-catenin During Wnt Signaling Cascadementioning
confidence: 99%
“…All tumor components were analyzed for LOH at the polymorphic markers DllS922, DllS988, and TH (Tyrosine Hydroxylase), which lie within or near the boundaries of a previously identified minimal region of overlap at 1 lp15.5, 4 ' 6 and DllS837, which maps within a group of potentially growth regulatory genes at 1 lp 15.3, a region that might represent a distinct SRO in breast cancer. [25][26][27] Six additional markers taken from the Genethon panel were used to characterize the SRO in cases with LOH. The order assigned (Fig.…”
Section: Methodsmentioning
confidence: 99%